#89 In-silico docking studies of some novel benzimidazole derivatives as anti-HIV-agents - Mohapatra, Tushar Ranjan (Journal of Pharmaceutical Chemistry, 2022)
Benzimidazole, a fused heterocycle bearing benzene and imidazole, has gained considerable attention from medicinal chemists worldwide. The moiety is of substantial importance because of its wide array of pharmacological activities, including but not limited to antibacterial, antifungal, anticancer, anti-inflammatory, analgesic, antimalarial, and antitubercular activity, etc. Considering the future scope of benzimidazoles against HIV, this work demonstrates molecular docking studies of a series of 7 benzimidazoles as potential anti-HIV agents. A molecular docking study was carried out on non-nucleoside inhibitory binding pocket (NNIBP) of HIV-1 RT (PDB ID:1RT2) receptor using Autodock Vina software. From our research, it was observed that compound 2b [2-(5,6-dibromo-1H-benzimidazole)-N-(4-ethylphenyl)-acetamide] exhibited the highest docking score of -9.5 kcal/mol and was found to have strong interactions with amino acid residues via hydrogen bond interactions with LYS103 amino acids of 1RT2. Thus, in the realm of developments of benzimidazoles as anti-HIV agents, it is concluded that compound 2b can be further studied to obtain suitable anti-HIV agents.